2000
DOI: 10.1097/00007632-200008150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Three- and Four-Level Anterior Cervical Discectomy and Fusion With Plate Fixation

Abstract: Three- and four-level modified Robinson cervical discectomy and fusion results in an unacceptably high rate of pseudarthrosis. The Cervical Spine Locking Plate alone does not appear to improve the arthrodesis rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
124
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(135 citation statements)
references
References 33 publications
6
124
1
4
Order By: Relevance
“…Wang et al [30] found that 18 % (7 of 40) of the patients had pseudarthrosis after three-level plated ACDF, and they observed no difference in fusion rates between plated and nonplated subgroups. Bolesta et al [3] reported a nonunion rate of 53 % (8/15 patients) for plated ACDF, the highest in the literature. This wide range of reported values can be explained by multiple factors, including differences in surgical technique, the number of levels grafted, the criteria used for pseudarthrosis, the length of brace use, and the length of follow-up.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Wang et al [30] found that 18 % (7 of 40) of the patients had pseudarthrosis after three-level plated ACDF, and they observed no difference in fusion rates between plated and nonplated subgroups. Bolesta et al [3] reported a nonunion rate of 53 % (8/15 patients) for plated ACDF, the highest in the literature. This wide range of reported values can be explained by multiple factors, including differences in surgical technique, the number of levels grafted, the criteria used for pseudarthrosis, the length of brace use, and the length of follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…This technique allows direct decompression of neural structures, restoration of disc height, and stabilization of the affected motion segments [2,3]. The success of the procedure relies on the development of a solid arthrodesis, although pseudarthrosis is not always associated with inferior outcome [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus it was desirable, and infact, using instrumentations gained an increase in lordotic curvature, as well as an increased primary stability with higher fusion rates [12,22,37,49,57,76,96,98]. However, it was scrutinized that with the advantage of anterior cervical spine instrumentations came their own shortcomings, such as implant related complications [12,20,37,115,117]. We could not confirm this observation in general, yet to be proven with a thorough evaluation of our clinical and radiographical results.…”
mentioning
confidence: 99%
“…The literature offers some hints that reconstruction of cervical lordosis might be favourable concerning clinical outcome and neurologic recovery [32,70,72,113]. However, the question of any influence of a distinct amount of lordotic realignement following the reconstruction of the multilevel decompressed cervical spine demands further investigation [12].…”
mentioning
confidence: 99%
“…However, this method has been associated with complications such as pseudoarthrosis or loss of solid fixation. Many of these complications are probably attributable to the inherent instability associated with these techniques [5,8,9,10,32,42,55]. Decompression via laminectomy is a commonly employed surgical intervention, although many clinicians have reported that the longitudinal results can be less than ideal.…”
mentioning
confidence: 99%